2007
DOI: 10.1354/vp.44-4-494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autologous Stem Cells on Immunohistochemical Patterns and Gene Expression of Metalloproteinases and Their Tissue Inhibitors in Doxorubicin Cardiomyopathy in a Rabbit Model

Abstract: Abstract. This study aims to investigate the expression of metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) in chronic doxorubicin cardiomyopathy in a rabbit model and to evaluate the effects of bone marrow-derived mesenchymal stem cell (MSC) transplantation in this disease. Thirtynine 3-month-old New Zealand rabbits were divided into 4 groups: group 1 (n 5 9) was the untreated control. Groups 2-4 were treated with 6 weeks of doxorubicin (3 mg/kg). Group 2 (n 5 6) received no further treatment. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
16
0
3
Order By: Relevance
“…Potentially, stem cells could alter collagenase activity or other enzymatic pathways responsible for pathologic heart wall thinning in injured myocardium, resulting in digestion of scar tissues and modification of extracellular matrix proteins [30]. Overexpression of collagen type I and III may protect infarcted myocardium from remodeling and dilation, but the increase in collagen synthesis in myocardium could result in stiffness and dysfunction of the damaged heart.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, stem cells could alter collagenase activity or other enzymatic pathways responsible for pathologic heart wall thinning in injured myocardium, resulting in digestion of scar tissues and modification of extracellular matrix proteins [30]. Overexpression of collagen type I and III may protect infarcted myocardium from remodeling and dilation, but the increase in collagen synthesis in myocardium could result in stiffness and dysfunction of the damaged heart.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF treated animals have shown low fibrosis tissue compared with MI and PBS groups, but no significant difference was observed with the dhUCM group. Previous studies had indicated that VEGF declined scar tissue in infarcted heart [54,55]. A possible explanation for the way VEGF decreases fibrosis formation is: VEGF induces the migration of endothelial, CSC and aortic smooth muscle cells to the infarcted area, triggers angiogenesis and facilitates the survival of vessels, promotes the proliferation and migration of cardiomyocytes and prevents their deaths by apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…De modo semelhante, Ivanová et al (2012) também não encontraram formas inativas e/ou ativas da MMP9 no tecido cardíaco de ratos. Por outro lado, Aupperle et al (2007), por meio de imunoistoquímica, encontrou aumento na imunomarcação de MMP1, MMP2 e MMP9 em cardiomiócitos de coelhos com cardiomiopatia induzida por DOX, comparativamente aos animais do grupo Sham.…”
Section: Discussionunclassified